2022
DOI: 10.1155/2022/1162218
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Dynamic Changes and Influencing Factors for the Quality of Life in Nursing Care after Lung Cancer Resection

Abstract: To investigate the dynamic changes and influencing factors for the quality of life in nursing care in patients with lung cancer after resection. Totally, 136 patients undergoing lung cancer resection in our hospital from January 2019 to January 2022 were prospectively enrolled as subjects. The quality of life was measured before and 1 and 2 weeks and 1, 3, 6, and 12 months after the operation to analyze the dynamic changes in the quality of life in nursing care. Clinical data of patients were collected at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…The decreased anxiety and sleep scores reflect that intervention may help improve patients' mental health and sleep quality, thus improving the QoL. Hu et al [9] conducted multivariate logistic regression analysis and found living alone, anxiety, and old age were risk factors, which are consistent with our Am J Cancer Res 2024;14(3):1278-1291 results. The identification and analysis of these risk factors not only contribute to an in-depth understanding of factors affecting the QoL of LC patients, but also provide useful implications for the design of targeted nursing interventions, which may help further improve the QoL and therapeutic effect of patients with LC.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The decreased anxiety and sleep scores reflect that intervention may help improve patients' mental health and sleep quality, thus improving the QoL. Hu et al [9] conducted multivariate logistic regression analysis and found living alone, anxiety, and old age were risk factors, which are consistent with our Am J Cancer Res 2024;14(3):1278-1291 results. The identification and analysis of these risk factors not only contribute to an in-depth understanding of factors affecting the QoL of LC patients, but also provide useful implications for the design of targeted nursing interventions, which may help further improve the QoL and therapeutic effect of patients with LC.…”
Section: Discussionsupporting
confidence: 84%
“…In recent years, due to advancements in both economic and medical fields, as well as the widespread adoption of comprehensive treatment approaches, the survival rates of LC patients have shown significant improvement. Recent advances in treatment have led to an increasing number of patients surviving with advanced lung cancer, presenting new and formidable challenges to tumor care [8,9]. In addition to suffering from symptoms associated with LC, such as pain, chemotherapy reactions, and sleep difficulties, LC patients also endure a Am J Cancer Res 2024;14(3):1278-1291 range of psychological and emotional distress, including anxiety, depression, despair, a sense of burden, and concerns about their families.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%